Projections of Climate-induced Future Range Shifts among Fruit Fly (Diptera: Tephritidae) Species in Uganda - Masembe, Charles; Isabirye, Brian Eriphaz; Rwomushana, Ivan; Nankinga, Caroline Kukiriza; Akol, Anne Margaret (Plant Protection Science, 2015)
The potential impact of future climate change on fruit fly species distribution was assessed in Uganda using two general circulation models (HADCM and CCCMA) and two future predicted CO2 emission scenarios (A2 and B2), under both full and no species dispersal modes. Future ranges were overall projected to decline by 25.4% by year 2050.Under full-dispersal, D. ciliatus > C. cosyra > B. invadens ranges were predicted to increase, while the rest are likely to decrease. In the no-dispersal scenario, a significant average decrease in size of niches is predicted. Range losses are predicted higher under B2 than A2. Future niches will likely shift to northern Uganda. The results should assist in the development of climate change adaptive pest management strategies.
Keywords: climate change; dispersal; Bacrocera; niche